Cu2Te solar cells fabricated by printing. (8th April 2013) - Nguyen, Duy–Cuong; Ito, Seigo
Cu2 Te particles were synthesised by ball milling and then printed on an In2 S3 /TiO2 /FTO–glass substrate, resulting in superstrate–structured solar cells. The as–prepared Cu2 Te particles were amorphous, but their crystallinity was improved after annealing at 400–650°C. The Cu2 Te particles annealed at 400°C, melted partially, and a completely melted Cu2 Te film was obtained at annealing temperatures of 600–650°C. The band gap of the Cu2 Te films annealed at 400–600°C was approximately 0.8 eV. The photovoltaic characteristics of the best full Cu2 Te cells were as follows: short–circuit current, 21 mA/cm²; open–circuit voltage, 0.24 V; fill factor, 0.3; and energy conversion efficiency, 1.57%. Thus, Cu2 Te with its low melting point and high photocurrent is a promising candidate absorber layer for solar cell applications.